2019
DOI: 10.3389/fnsyn.2019.00035
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Differentially Alters the Synaptic and Intrinsic Properties of D1R- and D2R-Expressing Medium Spiny Neurons in the Nucleus Accumbens

Abstract: Exposure to opioids reshapes future reward and motivated behaviors partially by altering the functional output of medium spiny neurons (MSNs) in the nucleus accumbens shell. Here, we investigated how morphine, a highly addictive opioid, alters synaptic transmission and intrinsic excitability on dopamine D1-receptor (D1R) expressing and dopamine D2-receptor (D2R) expressing MSNs, the two main output neurons in the nucleus accumbens shell. Using whole-cell electrophysiology recordings, we show, that 24 h abstine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…Data from Bonci and Williams (1996), Kang et al (1996Kang et al ( , 1998, Robinson and Kolb (1997), Robinson and Kolb (2004), Badiani et al (1999), Mansvelder and McGehee (2000), Dahchour and De Witte (2000), Uslaner et al (2001), Brown and Kolb (2001), Robinson et al (2002), Saal et al (2003), Amantea et al (2004), Hamilton and Kolb (2005), Nasif et al (2005), Kolb et al (2006), Kolb et al (2018), Huang et al (2007), Zhou et al (2007) McDevitt et al, 2019) and induces silent synapses on iMSNs via AMPA internalization (Graziane et al, 2016). Moreover, during withdrawal, opioid-generated silent synapses on iMSNs are eliminated (Graziane et al, 2016), and the intrinsic excitability of iMSNs is weakened (McDevitt et al, 2019). Given that MSNs create a dense network of lateral inhibition within the NAc, with ∼30% of iMSNs synapsing onto other iMSNs or dMSNs (Taverna et al, 2008), it is possible that opioidinduced disruptions in iMSN signaling could disrupt local NAc microcircuitry and facilitate aberrant C-BG-T network dynamics.…”
Section: Opioidsmentioning
confidence: 99%
“…Data from Bonci and Williams (1996), Kang et al (1996Kang et al ( , 1998, Robinson and Kolb (1997), Robinson and Kolb (2004), Badiani et al (1999), Mansvelder and McGehee (2000), Dahchour and De Witte (2000), Uslaner et al (2001), Brown and Kolb (2001), Robinson et al (2002), Saal et al (2003), Amantea et al (2004), Hamilton and Kolb (2005), Nasif et al (2005), Kolb et al (2006), Kolb et al (2018), Huang et al (2007), Zhou et al (2007) McDevitt et al, 2019) and induces silent synapses on iMSNs via AMPA internalization (Graziane et al, 2016). Moreover, during withdrawal, opioid-generated silent synapses on iMSNs are eliminated (Graziane et al, 2016), and the intrinsic excitability of iMSNs is weakened (McDevitt et al, 2019). Given that MSNs create a dense network of lateral inhibition within the NAc, with ∼30% of iMSNs synapsing onto other iMSNs or dMSNs (Taverna et al, 2008), it is possible that opioidinduced disruptions in iMSN signaling could disrupt local NAc microcircuitry and facilitate aberrant C-BG-T network dynamics.…”
Section: Opioidsmentioning
confidence: 99%
“…These changes often exhibit projection and cell-type specificity, are mediated by different AMPAR subtypes, may organize into different functional ensembles, and differentially regulate cocaine-elicited behaviors. Beyond cocaine, projection and cell-type specificities of NAc circuits have also been observed in seeking behaviors induced by other drugs of abuse as well as natural rewards, with similar and yet differential cellular and circuit features in each case 55 , 120 , 209 211 . It is important for future studies to define both the uniqueness and common ground underlying the ensemble, circuit, and behavioral correlates induced by these drug/reward experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that, although morphine can induce an overall structural plasticity in the MSNs of the CPu, it is unable to modify their passive membrane properties and intrinsic excitability. Interestingly, previous studies have demonstrated that repeated morphine exposure specifically alters the activity of the NAc MSNs which expressed the dopamine D2 receptors (D 2 R) [ 56 , 57 ]. Thus, as in our analysis we did not identify striatal MSNs subpopulations—e.g., direct- and indirect-pathway projection neurons—it remains to be investigated in future works whether morphine specifically mediates changes in one of them.…”
Section: Discussionmentioning
confidence: 99%